PENGARUH PROFITABILITAS, KEPEMILIKAN MANAJERIAL, DER DAN FCF TERHADAP NILAI PERUSAHAAN MELALUI DPR - Pertiwi, Nita Tiyas; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to test: (1) the influence of profitability, managerial ownership, debt policy and free cash flow to the dividend policy and firm value; (2) the influence of dividend policy to the firm value; (3) the influence of profitability, managerial ownership, debt policy and free cash flow to the firm value which is mediated by dividend policy. The population of this research is all manufacturing companies which are listed in Indonesia Stock Exchange in 2008-2014. In this research, the sample collection has been determined by using purposive sampling, and 238 companies have been selected as samples. This research is done by using multiple linear regressions technique and the mediated variable is product of coefficient method. The result of this research shows that: (1) profitability, managerial ownership and free cash flow have influence to the dividend policy and firm value; (2) debt policy does not have any influence to the dividend policy; (3) debt policy and dividend policy does not have any influence to the firm value; (4) dividend policy does not mediate the correlation of profitability, managerial ownership, debt policy and free cash flow to the firm value.Keywords: Profitability, Managerial Ownership, Debt Policy, Free Cash Flow, Dividend Policy, Firm Value